The legal qualification of the criminal complaint: problems and alternatives - Revilla Palacios, Ana María (2020)
The deficiencies in filing a criminal complaint, supported by the order to open investigation, lead to the subsequent annulment of the case after a lengthy process. Therefore, it becomes urgent that the competent authority duly justifies his examination and determinations, which although the Government Attorney General’s Office is responsible for criminal prosecution, it is the judge’s responsibility to control legality, and in this sense, assessing if the facts identifying the criminal actions are contained in the document containing criminal prosecutions. If so, the pertinent legal grounds should be indicated without changing the facts. This will contribute to eliminate excessive costs and the sensation of unpunishment derived from such technical deficiency flaws